The economics of patients undergoing periacetabular osteotomy for hip dysplasia: the financial relationship between physicians and hospitals. Issue 4 (10th August 2022) - Alter, Thomas; Fitch, Ashlyn; Bailey Terhune, E; Williams, Joel C
ABSTRACT: Periacetabular osteotomy (PAO) is the gold standard for treating hip dysplasia in patients with preserved articular cartilage. The aim of this study is to evaluate the financial relationship between facility and professional revenue for patients undergoing PAO for hip dysplasia and acetabular version abnormalities. All patients who underwent PAO for hip dysplasia by a single surgeon at a tertiary academic medical center between December 2016 and November 2020 were identified. Financial records for facility and professional services were reviewed and analyzed. The orthopedic charge multiplier, the dollars of facility charge created by a single dollar of orthopedic professional charge, and orthopedic net revenue multiplier, the dollars collected by the hospital for facility services generated for each dollar collected by the orthopedic surgeon, were calculated. A total of 36 patients were included in the study. The mean total charge for all patients was $144 939.35 ± $23 726.48 (range $109 002.71 to $227 290.20), and the average total revenue for all patients was $44 218.79 ± $12 352.97 (range $29 397.39 to $90, 830.62). The mean orthopedic charge multiplier was 2.47 ± 1.32 (range 0.78–6.53), and the net revenue collection multiplier was 8.62 ± 10.69 (range, 1.20–57.80). The majority of charges and revenue related to care of patients undergoing PAO return to the hospital. The significant mean orthopedic charge multiplier for this procedure increases the value of the service and the surgeon to hospital profitability. This information can help shape the relationship between the hospital and the surgeon and create a firm platform to advocate for program advancement.